Association between antenatal care visit and preterm birth: a cohort study in rural Bangladesh - Anisur Rahman; Monjur Rahman; Jesmin Pervin; Shaki Aktar; Syed Moshfiqur Rahman (BMJ Open)
Background Strengthening the antenatal care programme is suggested as one of the public health strategies to reduce preterm birth burden at a population level. However, the evidence so far available is inconclusive.Objectives To evaluate the association between antenatal care (ANC) visit and preterm birth; and also to explore to what extent the increased usage of ANC after the initiation of the Maternal, Neonatal and Child Health (MNCH) project in Matlab, Bangladesh, contributed to the reduction of preterm birth.Setting This population-based cohort study was conducted in Matlab, a subdistrict under Chandpur. The analysis was based on data collected from 2005 to 2009. In 2007, an MNCH project was initiated in the area that strengthened the ongoing ANC services.Participants In total, 12 980 live births with their mothers during the study period were included in the analysis.Analysis We performed logistic regression with generalised estimating equation models to evaluate the associations.Outcome measures Preterm birth.Results The number of ANC visits was associated with preterm birth in a dose-dependent way (p for linear trend <0.001). The adjusted odds of preterm birth were 2.4-times higher (OR 2.37, 95% CI 2.07 to 2.70) among women who received ≤1 ANC compared with women who received ≥3 ANC. We observed a significant reduction of preterm birth rates (OR 0.69, 95% CI 0.61 to 0.77) in the period after (2008 to 2009) MNCH project initiation in comparison to the period before (2005 to 2006). Controlling for ANC visits substantially attenuated this observed effect of the MNCH project on preterm birth (OR 0.88, 95% CI 0.77 to 0.99) (Sobel test of mediation p<0.001).Conclusions ANC visits are associated with decreased occurrences of preterm births. Strengthening the ANC services should be prioritised in countries with high preterm birth rates to reduce the preterm birth burden at the population level.